Budgeting for results : evaluating the utilization of performance measurement tool in the Modified Budgeting System (MBS) in Malaysia - Nor Azlina Ariffin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences,International Islamic University Malaysia, 2013)
The allocation and utilization of public funds have triggered reforms in public sector budgeting in governments around the world including Malaysia. Under the current Modified Budgeting System (MBS), the Malaysian government is highly expected to deliver an excellent performance. This study was undertaken to examine and analyze the utilization of performance measurement tool through its adoption and implementation in MBS in the activities of the Malaysian public sector. In addition, by adapting de lancer Julnes' utilization model, the relationship between factors of formal requirement, technical capacity, organizational culture and goal orientation with adoption and implementation of performance measurement tool were studied. The research is significant because for more than 20 years of MBS implementation, desired outcomes of prudent spending and better allocation of resources across activities through utilization of performance measurement in MBS are not that visible. The study presents and discusses empirical findings through a triangulation method involving the survey of 126 activities in the Malaysian public sector using SPSS and structural equation modeling (SEM) through PLS software, corroborated with structured interviews of 30 respondents. Major findings indicate that public sector organizations have developed output and input measures more than outcome and efficiency measures. Only performance measurement tools in terms of efficiency, quantity of output, standard duration of time to produce an output, quality of output and results of services are mostly used to manage activities in organizations. In addition, top management and policy are the main sources of influence in the utilization of performance measures. Surprisingly, the practice of performance measurement is mainly prevalent among the management employees as compared to non-management employees. The findings of this study support the hypothesized relationships proposed in the theoretical model: there are significant positive relationships between adoption of performance measurement tool and implementation of performance measurement tool, formal requirements and adoption, formal requirements and technical capacity, technical capacity and adoption, organizational culture and goal orientation as well as goal orientation and adoption. The results also provide strong evidence of mediation of adoption on formal requirements and implementation, of adoption on technical capacity and implementation, of adoption and goal orientation and implementation, and of goal orientation on organizational culture and adoption. The results of this study also demonstrate the need for effective training on the use of performance measurement tool in MBS, providing incentives to encourage its use, instilling the right values in the organizations, involvement of the top management, stronger monitoring and integration of the budgeting system with other existing management systems.